OTM7 - Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
In the period between October 2016 and June 2018 Vejdirektoratet has completed updating of the OTM model, version 6.1. The project includes three important improvements: Modelling of bicycle transport Estimating new values of travel time Updating of the route choice model and the demand model Apart of the above improvements the zonal system has been improved dramatically, the model base matrices are built based on TU data and GPS data, and the road network has been improved. The new OTM model, i.e. OTM 7, will be applied in autumn 2018 in the Copenhagen East Ring Road feasibility project.